Use of Vegetable Waste Extracts for Controlling Microstructure of CuO Nanoparticles: Green Synthesis, Characterization, and Photocatalytic Applications - Hameed Ullah; Zia Ullah; Aliya Fazal; Muhammad Irfan (Journal of Chemistry)
Chemical syntheses involve either hazardous reactants or byproducts which adversely affect the environment. It is, therefore, desirable to develop synthesis processes which either do not involve hazardous reactants or consume all the reactants giving no byproducts. We have synthesized CuO nanoparticles (NPs) adhering to some of the principles of green chemistry. The CuO NPs have been synthesized exploiting extracts of vegetable wastes, that is, Cauliflower waste and Potatoes and Peas peels. The extracts were aimed to work as capping agents to get control over the microstructure and morphology of the resulting CuO NPs. The green synthesized CuO NPs were characterized to explore the microstructure, morphology, optical bandgaps, and photocatalytic performances. XRD revealed that the CuO NPs of all the samples crystallized in a single crystal system, that is, monoclinic. However, the morphologies and the optical bandgaps energies varied as a function of the extract of vegetable waste. Similarly, the CuO NPs obtained through different extracts have shown different photocatalytic activities. The CuO NPs produced with extract of Cauliflower have shown high degradation of MB (96.28%) compared to obtained with Potatoes peels (87.37%) and Peas peels (79.11%).